Direito humano ao desenvolvimento: universalização, ressignificação e emancipação - Fachin, Melina Girardi (2013)
This thesis has as main goal to propose a renewed critical and constructive study of the human right to development and its respective reconfiguration as a theoretical category of practical possibilities, capable of overcoming the convenience of the universal human rights discourse experienced in our times. In this context, from a revised perspective, also pursues, as a specific object, to confront the paradox of partial universalization which is, at the same time, generator and generated by a fragmented conception of human rights which breaks with the provisions of the contemporary idea of these rights reflected in the Universal Declaration of Human Rights (1948). This is justified by the emancipatory possibility that can arise of the universalization of human right to development, seen through the lenses inherited by the human rights approach. This perspective has as an outcome the normative and material empowerment of human beings and as consequence the process of expansion of human liberties and (re)signification of a dignified existence from concrete realities. The theme, here proposed, will be focused from a bibliographical approach that combines, in a dialectical complementarity, the international bias with the domestic level of protection of human rights